Analysis of Students' Physics Learning Outcomes Using E-learning During Covid-19 Pandemic - Sari, S. Salmiah; Zul, Marhamah; Haris, Abdul (Universitas Muhammadiyah Makassar, 2022)
This study aims to analyze the physics learning outcomes of students with e-learning during the Covid-19 pandemic at SMA Negeri 12 Bone. This type of research is a survey with a quantitative approach. Data analysis used descriptive statistics in the form of percentages. The study involved 105 students of class XI at SMA Negeri 12 Bone as respondents who had studied physics with e-learning during the Covid-19 pandemic. The results showed that there were 1.91% of students in the very high category, 7.61% in the high category, and 18.10% in the medium category. While the distribution of the highest score is in the range of scores of 41-55 with a percentage of 38.10%. This range of scores is in a low category and then followed by the distribution of the second-highest score in the very low category with a percentage of 34.28%. From the results of the study, it can be concluded that the average cognitive physics learning outcomes of students with e-learning during the covid-19 pandemic at SMA Negeri 12 Bone were in the low and very low categories.